The Making of Critical Consciousness among Marinalizes High School Students in Sociology Education - Suarti, Suarti (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study explores the formation of critical awareness among high school students from marginalized backgrounds in the context of sociology learning. Motivated by the socioeconomic limitations that often hinder reflective thinking and understanding of social injustice, the research employs a qualitative exploratory descriptive approach. Data were collected through open-ended online questionnaires completed by 85 students from low-income families in Baubau City, Southeast Sulawesi. Thematic analysis reveals three stages of critical awareness development: (1) initial awareness, recognizing social injustice; (2) critical analysis, fostered through real-life case learning; and (3) orientation to action, though still limited to activities like information sharing or peer discussions. Key supporting factors include teachers’ reflective questioning, relevance of learning materials, and peer solidarity, while main barriers involve limited access to literature and low reading habits. The study concludes that sociology learning can effectively foster critical awareness among marginalized students, with outcomes shaped by instructional strategies and access to knowledge. It highlights the importance of contextual, participatory learning designs and calls for further mixed-methods research to deepen insights into the dynamics of critical awareness formation.